The sfp-type 4'-phosphopantetheinyl transferase Ppt1 of Cochliobolus miyabeanus controls development and pathogenicity - Mohd Zainudin, Nur Ain Izzati; Turgeon, Barbara Gillian (Department of Biology, Faculty of Science, Universiti Putra Malaysia, 2016)
In filamentous fungi, the sfp-type 4’-phosphopantetheinyl transferase Ppt1 is required for activation of some of the enzymes for lysine biosynthesis, and peptide/polyketide secondary metabolites. Cochliobolus miyabeanus is a pathogen of brown spot disease on rice. In this study, C. miyabeanus PPT1 mutants were derived from the wild-type (WT) strain WK1C (ATCC 56640, MAT1-2). The PPT1 gene was deleted using the split marker method. The 5’ and 3’ flanking sequences of the predicted open reading frame of each target gene were amplified from WT using two specific primer sets (CmPPT1UF1, CmPPT1UR1, CmPPT1DF1 and CmPPT1DR1) that matched the upstream and downstream PPT1 gene flanking sequences. Transformation of C. miyabeanus was carried out as previously described (Inderbitzin et al., 2010; Oide et al., 2006), with a slight modification. Deletion of the PPT1 in the rice pathogen, C. miyabeanus was verified by Polymerase Chain Reaction (PCR) amplification using three diagnostic primer sets. Three independent C. miyabeanus mutants (Cmppt1-1, Cmppt1-4 and Cmppt1-8) were generated. Growth of all Cmppt1 mutants was reduced to 50.5% compared to WT and their colony surfaces were hydrophilic. In addition, ppt1 mutants of C. miyabeanus were also reduced in tolerance to oxidative stress and iron depletion. As expected, mutants were albino since they cannot produce the polyketide melanin and were auxotrophic for lysine because they lack an α-aminoadipate reductase. Interestingly, the yielded strains were significantly reduced in virulence to rice. Because C. miyabeanus ppt1 mutants make no or very few conidia, virulence was tested by inoculating a mycelial suspension of the mutants with supplemental lysine into rice leaves. At 10-day post inoculation, WT had developed large dark brown necrotic areas (6.10 ± 1.41 mm) surrounded by chlorotic halos. Cmppt1 mutants caused much less damage and appeared as light brown patches without obvious chlorosis (3.69 ± 0.86 mm), in most cases.